Configuração das elites política e econômica em São Carlos/SP – 1873 a 1904 - Conceição, Carla Fernandes da (2015)
Through the transition from Empire to Republic in Brazil, coffee farmers constituted the economic and political elite on the municipal, state and federal levels. Starting from a Historical Sociology perspective and based on classical authors – Mosca, Pareto and Michels – the present research aimed to investigate the coffee farmers presence within the elite of São Carlos city, in São Paulo state, Brazil. With this respect, studying the configuration of those farmers was shown to be relevant to comprehend the bonds created and maintained between elite members, specifically between the years 1873 and 1904.